Peculiarities of Legal Regulation of Non-Discrimination on Gender Basis while Being Employed - A. V. Kuchko (Law and Safety)
The Constitution of Ukraine enshrines and guarantees the right to labor as an opportunity to earn a living by work that a person freely chooses or agrees to. However, the current conditions indicate that the consolidation and guarantee of everyone’s right to labor is not an unconditional evidence of its inviolability, the absence of unjustified restrictions and obstacles to its realization. One of such obstacles to the realization of this right is gender discrimination, which violates the balance of male and female labor at the labor market and creates an imbalance in the harmonious development of labor and closely related relations. In this regard, the author has emphasized the importance of the existence of a wide range of effective legal principles in the national labor legislation for non-discrimination while employment, in particular on the grounds of sex, as well as an effective mechanism for their realization.